Presentation of Acute Bronchitis in Adolescents with Various Comorbid Pathologies - Tog’aydullayeva Dildora Dilmurodovna (American Journal of Bioscience and Clinical Integrity, 2025)
This article discusses the frequency, types, etiology, prevention and effectiveness of treatment methods for bronchitis in children with other comorbid diseases. According to literature data, bronchitis on the background of atopic dermatitis is characterized by excessive bronchial secretions and is accompanied by respiratory failure, while bronchitis on the background of thymomegaly is accompanied by prolonged febrile fever, as well as microcirculation disorders. Bronchitis in children with connective tissue dysplasia has a recurrent nature with prolonged symptoms of inflammation. When bronchitis with concomitant pathology is detected, it is necessary to add additional diagnostic and treatment methods.